Characterization And Functional Study Of Stress-Associated Protein In Rice And Arabidopsis - Mohd Roszelin, Sitti' Aisyah; Mohd Hazbir, Nur Aminah; Jumali, Siti Sarah; Shakri, Tasneem; Md Isa, Nurulhikma (Malaysian Applied Biology, 2023)
Environmental stress can hinder the growth and development of crops, thereby reducing productivity. Plants can adapt to changing environments through various morpho-physiological changes, transcriptome regulation, signaling, translational and post-translational modifications. Stress Associated Proteins (SAPs) have been shown to play a crucial role in plant adaptation to biotic and abiotic stressors. They are encoded by a family of genes that produce a zinc finger protein with A20 and/or AN1 domains at either their N or C-terminal ends. Therefore, this study focused on understanding the role of the Oryza sativa SAP gene family (OsSAPs) in response to drought and salinity stress. In-silico analysis revealed that most of the OsSAP family members were upregulated by stress; two highly inducible OsSAP genes were also upregulated in response to stress under a rice-specific background. To study gene function, an Arabidopsis transformation system was employed using three genotypes: Col-0 (wild type), overexpressed transgenic OsSAP8, and atsap2 T-DNA knockout mutant. Arabidopsis AtSAP2 gene, which is homologous to rice OsSAP8, was used as a comparison to the loss of function mutation in Arabidopsis. Morphophysiological analysis showed that the atsap2 mutant displayed a sensitive phenotype to drought and salinity stress through low relative chlorophyll content and delayed inflorescence development and flowering as compared to Col-0 and transgenic OsSAP8. This suggests that the abolished atsap2 gene may contribute to reduced stress tolerance in plants. In contrast, transgenic OsSAP8 overexpression demonstrated tolerance to drought and salinity stress by maintaining relative chlorophyll content under both stress conditions, indirectly reflecting sustained photosynthetic machinery and stable photosynthetic rate. Further investigation, such as measuring the photosynthesis rate, is required to establish the correlation between chlorophyll data and photosynthesis activity.